Reliability analysis of dynamic systems : efficient probabilistic methods and aerospace applications - Wu, Bin (Elsevier and Shanghai Jiao Tong University Press aerospace series., 2013)
Featuring aerospace examples and applications, Reliability Analysis of Dynamic Systems presents the very latest probabilistic techniques for accurate and efficient dynamic system reliability analysis. While other books cover more broadly the reliability techniques and challenges related to large systems, Dr Bin Wu presents a focused discussion of new methods particularly relevant to the reliability analysis of large aerospace systems under harmonic loads in the low frequency range. Developed and written to help you respond to challenges such as non-linearity of the failure sur.